(untitled) (El Hilo de la Fabula, 2020)
Singable translations of lyrics can lead to rich cultural exchanges and, at the same time, demand a special creativity. Although there are numerous elements to consider to achieve a successful version, many critics believe that one must find a domestication faithful to the semantics of the song and thus a singable equivalence. Nevertheless, a generative translation (Bradford, 2013) may provoke greater growth of the original expression and infinite pleasure. Two examples will be analyzed: one from Brazilian music and the other from Juan Gelman’s Com/posiciones.